A Stress-Responsive Signaling Network Regulating Pseudohyphal Growth and Ribonucleoprotein Granule Abundance in Saccharomyces cerevisiae - Mutlu, Nebibe (Genetics, 2019)
The budding yeast Saccharomyces cerevisiae undergoes a stress-responsive transition to a pseudohyphal growth form in which cells elongate and remain connected in multicellular filaments. Pseudohyphal growth is regulated through conserved signaling networks that control cell growth and the response to glucose or nitrogen limitation in metazoans. These networks are incompletely understood, and our studies identify the TORC1- and PKA-regulated kinase Ksp1p as a key stress-responsive signaling effector in the yeast pseudohyphal growth response. The kinase-defective ksp1-K47D allele results in decreased pseudohyphal morphology at the cellular and colony level, indicating that Ksp1p kinase signaling is required for pseudohyphal filamentation. To determine the functional consequences of Ksp1p signaling, we implemented transcriptional profiling and quantitative phosphoproteomic analysis of ksp1-K47D on a global scale. Ksp1p kinase signaling maintains wild-type transcript levels of many pathways for amino acid synthesis and metabolism, relevant for the regulation of translation under conditions of nutrient stress. Proteins in stress-responsive ribonucleoprotein granules are regulated post-translationally by Ksp1p, and the Ksp1p-dependent phosphorylation sites S176 in eIF4G/Tif4631p and S436 in Pbp1p are required for wild-type levels of pseudohyphal growth and Protein Kinase A pathway activity. Pbp1p and Tif4631p localize in stress granules, and the ksp1 null mutant shows elevated abundance of Pbp1p puncta relative to wild-type. Collectively, the Ksp1p kinase signaling network integrates polarized pseudohyphal morphogenesis and translational regulation through the stress-responsive transcriptional control of pathways for amino acid metabolism and post-translational modification of translation factors affecting stress granule abundance.